2008
DOI: 10.1158/1055-9965.epi-07-0066
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Normal Rectal Mucosa, Baseline Adenoma Characteristics, and Risk of Future Adenomas

Abstract: Low apoptosis in the normal rectal mucosa has been associated with colorectal adenomas in cross-sectional studies. It is unknown whether apoptosis can predict the occurrence of new adenomas. We evaluated whether apoptosis at baseline colonoscopy, as well as patient and adenoma characteristics, could predict future occurrence of adenomas. Study subjects were participants in the Diet and Health Study III, a crosssectional study of adenoma risk factors between August 1998 and March 2000. At baseline, subjects und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(40 reference statements)
0
11
0
1
Order By: Relevance
“…Our studies on the effect of previous adenomas are inconclusive but potentially suggest contributions from both longer term field carcinogenesis and tumor-related factors analogous to our data for microvascular blood content (38). Other groups have shown that rectal apoptosis rate predicts future development of neoplasia, suggesting that the markers of field carcinogenesis may reflect immediate as well as long-term risk (44). Thus, the utility of rectal LEBS for postpolypectomy surveillance will need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies on the effect of previous adenomas are inconclusive but potentially suggest contributions from both longer term field carcinogenesis and tumor-related factors analogous to our data for microvascular blood content (38). Other groups have shown that rectal apoptosis rate predicts future development of neoplasia, suggesting that the markers of field carcinogenesis may reflect immediate as well as long-term risk (44). Thus, the utility of rectal LEBS for postpolypectomy surveillance will need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study having previously measured the levels of apoptosis (using morphology from H&E stained specimens) within the normal rectal mucosa of patients attending for colonoscopy for a variety of reasons, but without colitis, familial adenomatous polyposis (FAP), previous colorectal cancer resection, previous colon cancer or adenoma, then correlated this previously measured apoptosis score with the number, size, histological type, and degree of atypia of polyps found at a subsequent follow-up colonoscopy (54). The followup population included patients with polyps at baseline who returned for follow-up of these, and patients without polyps at baseline but who were scheduled for a clinically indicated colonoscopy.…”
Section: Apoptosis In Adenomasmentioning
confidence: 99%
“…The findings were of an inverse relationship between apoptosis and the development of new adenomas, and subjects in the highest tertile of apoptosis were less likely to have adenoma recurrence. Because some patients who initially do not show adenomas will develop them in the future, but will be unlikely to enter surveillance programs because of the lack of an index polyp, it was suggested therefore by the authors, that apoptosis might be used to asses risk of future polyp development, but added that the current methods to assess apoptosis are too ''tedious'' to be clinically useful (54).…”
Section: Apoptosis In Adenomasmentioning
confidence: 99%
“…Our group has shown that patients with adenoma have reduced apoptosis in their normal mucosa, demonstrating a field effect that predisposes the individual to a higher risk of developing precancerous adenomas [14,15]. We hypothesized that SOCS3 might be a good biomarker of colorectal neoplasia risk, but contrary to expectation the study was negative.…”
Section: Discussionmentioning
confidence: 85%